Vertical spindle surface grinding of AISI 1020 and A36 steels using duplex grade vitrified abrasive segments. Issue 9 (December 2016) - Jackson, M.; Whitfield, M.; Burgess, J.
Abstract The studies described in this paper focus on the wear behavior of duplex grade abrasive segments grinding AISI 1020 and A36 steels on a vertical spindle surface grinding machine (VSSG). The study focuses on the behavior of the abrasive segment and how it contributes to significant changes in the grinding ratio and the type of wear that is occurring under grinding conditions where short chips are generated (roughness ratio, λ > 1) and accumulate in the graded structure of the abrasive segment. The paper discusses the kinematics of the VSSG process, the mechanisms of wear in abrasive and bonded grains, the VSSG experiments performed, and the results generated in terms of segment wear and the resulting roughness of the ground surfaces. The analysis of the results concludes by stating that duplex graded segments are useful in controlling the phenomena of "chip crowding, " although this may lead to "parasitic wear" to take place that may negatively affect segment performance in VSSG operations. In this respect, the paper addresses the type of abrasive grain to be used during VSSG operations. The studies described in this paper may be useful to manufacturing engineers who use VSSG operations and are responsible for their development.